Effects of PSMA1 on the differentiation and lipid deposition of bovine preadipocytes - Sheng Li; Chengzhen Chen; Hao Jiang; Jiabao Zhang; Qian Zhou; Yan Gao; Bao Yuan; Mingjun Zhang (Revista Brasileira de Zootecnia)
ABSTRACT In this study, our goal was to clarify the role of proteasomal subunit α-1 (PSMA1) in both the differentiation of preadipocytes and the accumulation of lipids in adipocytes. Preadipocytes from healthy one-day-old calves were collected, isolated, and cultured in vitro. The expression pattern of the PSMA1 gene was explored during the differentiation of bovine preadipocytes firstly. Then, the expression of the PSMA1 gene was inhibited by transfection of a chemically synthesized small interfering RNA (siRNA) before differentiation. After induction of differentiation, the mRNA levels of key regulating genes involved in preadipocyte differentiation and the lipid content of mature adipocytes with and without inhibition of PSMA1 were detected by qRT-PCR and oil red O staining, respectively. The data showed that PSMA1 mRNA was differentially expressed during the differentiation of bovine preadipocytes under normal culture conditions in vitro. The expression level of peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT enhancer-binding protein alpha (C/EBPα), and lipoprotein lipase (LPL) were significantly decreased in the transfected PSMA1-siRNA group compared with those in the control group, and the mRNA levels of the preadipocyte factor-1 (Pref-1) were significantly upregulated in the transfected PSMA1-siRNA group compared with those in the control group. In addition, significantly fewer lipid droplets were formed by adipocytes transfected with PSMA1-siRNA than by the negative control group (adipocytes transfected with NC-siRNA). Therefore, PSMA1 plays an important role in differentiation and lipid deposition.